Presentation: A look at South Andean art - Valle Rondón, Fernando (2011)
The double number that we present on this occasion brings together a set of collaborations related to the world of art in the southern Andes, where the iconographic is connected with the approaches of cultural and social history, as well as anthropology. Thus, the articles that make up the dossier of this edition —especially the contributions of the three academics from North American universities— have as a common denominator the study of the iconography present in colonial pictorial art, revealing the rich underlying symbology in Andean art and its connections with multifaceted social and cultural factors.